A Flexible Nested Sodium and Proton Coil Array with Wideband Matching for Knee Cartilage MRI at 3 Tesla - Brown, Ryan (Magn Reson Med, 2015)
PURPOSE: We describe a 6×2 channel sodium/proton array for knee MRI at 3 Tesla. Multi-element coil arrays are desirable because of well-known signal-to-noise ratio advantages over volume and single-element coils. However, low coil-tissue coupling that is characteristic of coils operating at low frequency can make the potential gains from a phased array difficult to realize. METHODS: The issue of low coil-tissue coupling in the developed six channel sodium receive array was addressed by implementing 1) a mechanically flexible former to minimize coil-to-tissue distance and reduce the overall diameter of the array and 2) a wideband matching scheme that counteracts preamplifier noise degradation caused by coil coupling and a high quality factor. The sodium array was complemented with a nested proton array to enable standard MRI. RESULTS: The wideband matching scheme and tight-fitting mechanical design contributed to greater than 30% central SNR gain on the sodium module over a mono-nuclear sodium birdcage coil, while the performance of the proton module was sufficient for clinical imaging. CONCLUSION: We expect the strategies presented in this work to be generally relevant in high density receive arrays, particularly in x-nuclei or small animal applications, or in those where the array is distant from the targeted tissue.